2018
DOI: 10.1111/acem.13319
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Emergency Department Acuity

Abstract: Emergency Severity Index had the strongest association with PHAC followed by CMI and annual ED volume. Academic status captures variability outside of that explained by ESI, CMI, annual ED volume, percentage of Medicare patients, or patients per attending per hour. All measures combined only explained only 42.6% of PHAC variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…In past decades, various screening tools have been incorporated into the triage systems to identify patients at a higher risk of clinical deterioration in acute care settings [ 4 , 5 ]. These instruments use physiological parameters, such as vital signs, to measure illness acuity (general level of patient illness, urgency for clinical intervention and intensity of resource utilisation) [ 6 ]. Previous studies have shown that tools such as the National Early Warning Score (NEWS) and the quick Sequential Sepsis-Related Organ Failure Assessment (SOFA) can be used to identify patients with infection who are at a higher risk of mortality in the hospital [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, various screening tools have been incorporated into the triage systems to identify patients at a higher risk of clinical deterioration in acute care settings [ 4 , 5 ]. These instruments use physiological parameters, such as vital signs, to measure illness acuity (general level of patient illness, urgency for clinical intervention and intensity of resource utilisation) [ 6 ]. Previous studies have shown that tools such as the National Early Warning Score (NEWS) and the quick Sequential Sepsis-Related Organ Failure Assessment (SOFA) can be used to identify patients with infection who are at a higher risk of mortality in the hospital [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that factors such as time of day; number of active patients on a resident’s list; current National Emergency Department Overcrowding Scale (NEDOCS) score; 32,33 door‐to‐registration time; door‐to‐bed time; door‐to‐physician time; laboratory and imaging turnaround times; transportation times to laboratory, x‐ray, and CT; and location of service within the ED—such as high‐acuity zones, lower‐acuity zones, or fast‐track—may additionally affect the throughput metrics for a given visit and represent possible sources of variability in the outcome measures of the study. We considered controlling for acuity, however Emergency Severity Index (ESI) was the only readily available proxy measure for acuity and has been shown to have only modest correlation with acuity 34 . We therefore elected not to control for ESI because we felt that the additional complexity added to the models outweighed the modest benefit afforded by the ESI’s ability to discriminate acuity.…”
Section: Discussionmentioning
confidence: 99%
“…We considered controlling for acuity, however Emergency Severity Index (ESI) was the only readily available proxy measure for acuity and has been shown to have only modest correlation with acuity. 34 We therefore elected not to control for ESI because we felt that the additional complexity added to the models outweighed the modest benefit afforded by the ESI's ability to discriminate acuity. These unmeasured sources of variability in the endpoints serve as confounders that limit the ability to detect a difference in the control and intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…As reflected in our study, a crucial factor which can impact ED waiting times is triage. The primary goal of triage in the emergency department is to facilitate the treatment prioritization of patients based on the urgency of patients’ symptoms and vital signs [23]. Acuity level is an important index used in triage where a lower acuity level equates to less severe symptoms and vital signs.…”
Section: Discussionmentioning
confidence: 99%